2021
DOI: 10.1016/j.nicl.2021.102761
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal effective connectivity in the sensory network in writer’s cramp

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…It is considered a motor network disorder including the sensorimotor cortex, basal ganglia, thalamus and cerebellum and provides a model for other forms of task specific dystonia areas (18)(19)(20)(21). Several studies demonstrated impaired sensory function (13,(22)(23)(24)(25)(26)(27), abnormal reorganization of the somatosensory cortex (S1) (28, 29) and sensorimotor integration (30) as result of maladaptive neural plasticity (31), alterations in motor planning with a lack of neuronal inhibition (13, 17), and cerebellar dysfunction (19,32,33). These areas are also involved during writing (34-36).…”
Section: Pathophysiology Of Writer's Crampmentioning
confidence: 99%
“…It is considered a motor network disorder including the sensorimotor cortex, basal ganglia, thalamus and cerebellum and provides a model for other forms of task specific dystonia areas (18)(19)(20)(21). Several studies demonstrated impaired sensory function (13,(22)(23)(24)(25)(26)(27), abnormal reorganization of the somatosensory cortex (S1) (28, 29) and sensorimotor integration (30) as result of maladaptive neural plasticity (31), alterations in motor planning with a lack of neuronal inhibition (13, 17), and cerebellar dysfunction (19,32,33). These areas are also involved during writing (34-36).…”
Section: Pathophysiology Of Writer's Crampmentioning
confidence: 99%